DYNAMICS OF AGE STRUCTURE AND HEALTH STATUS OF PINE STANDS CREATED ON OLD ARABLE LANDS IN THE KHARKIV HILLSLOPE REGION DURING 2001–2011 - Mihaylichenko, O. A.; Ustsky, I. M. (Forestry and Forest Melioration, 2018)
Introduction Massive planting of pine trees on old arable lands of the Left bank of the Siversky Donets river in Kharkiv hillslope region was performed in two stages: the first one, at the beginning of the XIXth century, for fixing shifting sands; the second one, during 1947–1960, to afforest poorly productive agricultural land and to overplant and restore the previously created areas of pine forests. There are groups of trees with shorter, fade or yellowing needles in the 15–20-year-old pine plantations of the first generation on old arable lands, mainly after the first tending felling. Every year the number of such trees increases. In place of the dried out trees the gaps are formed at the border of which there is a constant loss of growing pine trees. Drying out foci are progressively expand, and in some cases the stand may become sparse one as early as in 30–40 years. The intensity of the drying depends on many factors, including the humidity condition of the area, special characteristics of the soil, prior use, climate, and forest management. The aim of the research is to assess the current state of pine plantations created at different times on old arable lands, including the spread of annosum root rot (Heterobasidion annosum (Fr.) Bref.) foci for the period from 2001 to 2011. Materials and methods The objects of research were pine plantations of different ages grown in the territory of the State Enterprise “Vovchanske Forest Economy” of Kharkiv Regional Administration of Forest and Hunting Management, created on old arable lands of the left bank of Siversky Donets river. The dynamics of the areas of pine stands affected by annosum root rot was analyzed by forest inventory data of the State Enterprise “Vovchanske Forest Economy” as of 2001 and 2011. The age distribution of the areas of the stands affected by annosum root rot was carried out by the degree of damage based on the scale of pine stands growth disturbance caused by annosum root rot. Results The area of pine plantations created on old arable lands of the State Enterprise “Vovchanske Forest Economy” has been almost unchanged for the period of 2001–2011. Based on forest management data of 2001, the total area of pine plantations of the studied forestries is 5,773 hectares. As of 2001, the area of plantings affected by annosum root rot accounted for 2,323.1 hectares (40.2 % of the total area of pine stands). Over the last revision period, as of 2011, the focal area had decreased by 82 hectares and was 2,240.8 hectares which are 38.4 % of the total pine area. As of 2011, about 280 hectares of pine stands affected by annosum root rot in a medium and strong degree were observed in State Enterprise “Vovchanske Forest Economy” that is 8 times goes beyond the area of such plantations as of 2001. Conclusions On the old arable lands of the left bank of the Siversky Donets river in Kharkiv hillslope region (State Enterprise “Vovchanske Forest Economy”), for the period 2001–2011, a slight decrease in areas of pine stands affected by annosum root rot is mainly due to clear sanitation felling in affected plantations of age classes VIII–X resulting in the increase of the young stands area. For the period of 2001–2011, the share of plantations affected by Heterobasidion annosum increased in the stands which had turned from ІV into V and from VІІІ into ІХ age classes. By the degree of damage, the areas of the trees slightly affected by annosum root rot had decreased in the stands under the age of 50 years for this period and had insignificantly increased in older stands. A significant increase of the area was detected for the 21–50-year-old stands affected in medium degree (9 times) and for the stands over the age of 50 years (18 times). The areas of the stands damaged in high degree had increased in 3 times for the stands over the age of 50 years mostly.